Reflections on public policies for education in human rights in Brazilian higher education - Daniel de Mello Massimino; Danielle Anne Pamplona (Arizona State University, 2017)
More than 50% of residents of Brazilian largest cities agree with the phrase a "good bandit is a dead bandit," but at the same time recognize the universality and relevance of human rights. This apparent paradox can only be unveiled by human rights education (or EDH), which is consolidated as public policy in that its bases its actions in bringing about constitutional principles, assuming a role of extreme importance, not only because of allowing to citizens to have contact with the contents of these DH concepts, but also because they are objectives of education recognized in the Constitution, the full development of the person, his preparation for the exercise of citizenship and his qualification for work such goals only being achieved with an education to enable individuals to understand their own humanity. It intends to explore this public policy by addressing the "policy cycle", which is used as a methodological standard approach, in order to answer the question on how to set up the cycle of public policies for HRE in higher education, and to what extent public policy can contribute to the installation of a new culture of human rights.